Measurement of Tooth Brushing Frequency, Time of Day and Duration of Adults and Children in Jakarta, Indonesia - Rahardjo, Anton; Maharani, Diah A.; Kiswanjaya, Bramma; Idrus, Erik; Nicholson, Julie; Cunningham, Paul J.; Schäfer, Fred (UI Scholars Hub, 2014)
Epidemiological study of tooth brushing is essential to evaluate dental health of a country. Objective: To obtain data on tooth brushing frequency, time of day and duration from adults and children in Jakarta, Indonesia. Methods: Toothbrushes containing data loggers were distributed to 120 random families in Jakarta to record how many times a day, when and for how long subjects brushed their teeth. The families were each composed of a mother, father and two children aged between 6 and 15 years. Results: The mean brushing frequency of the population was 1.27 times per day. The majority of the tooth brushing (46%) was performed in the morning. The mean tooth brushing duration of this population was 57.29 seconds. The mothers’ tooth brushing frequencies tended to be higher than that of the other family members, and the fathers tended to brush their teeth longer. Conclusion: Effective education aimed at increasing both the duration and frequency of tooth brushing from once to twice per day is urgently required in Indonesia.